Long noncoding RNAs in osteosarcoma via various signaling pathways. Issue 6 (6th April 2020) - Han, Jinming; Shen, Xiaohan
Abstract: Osteosarcoma is one of the most commonly seen bone malignancies with high incidence rate in both children and adults. Although the regulatory network of osteosarcoma has been greatly concerned for years, the mechanisms regarding its oncogenesis and development are still not clear. Recent discoveries have revealed that long noncoding RNAs (lncRNAs) play a crucial role in the development, progression, and invasion of osteosarcoma. Deregulated expression of lncRNAs has been found to participate in the regulation of various signaling transduction pathways in osteosarcoma. This review summarized roles of lncRNAs in the pathogenesis, development, and potential therapeutic of osteosarcoma via different signaling pathways. For examples, MALAT1, CCAT2, FER1L4, LOXL1‐AS1, OIP5‐AS1, PVT1, DBH‐AS1, and AWPPH regulate PI3K/Akt signaling; AWPPH and BE503655 regulate Wnt/β‐catenin signaling; NKILA and XIST regulate NF‐κB signaling; MEG3 and SNHG12 regulate Notch signaling; FOXD2‐AS1 and LINK‐A regulate HIF‐1α signaling; GClnc1 and HOTAIR regulate P53 signaling; ZFAS1, H19, and MALAT1 regulate MAPK, Hedgehog and Rac1/JNK signaling, respectively.